Climate Change Regulations Bank Lending and Real Effects - Miguel, Faruk (The World Bank, 2022)
This paper analyzes how capital requirements from environmental risk exposure affect bank lending to the corporate sector, and how these effects transmit to real economic activity and greenhouse gas emissions. It exploits the introduction of a policy in Brazil that required banks to incorporate environmental risks into their capital assessments. Using comprehensive credit data, the paper finds that the policy induces large banks to reallocate their lending away from exposed sectors. The credit contraction has no substantial impact on the real activity and greenhouse gas emissions of these sectors, as smaller banks expand their lending. However, the policy triggers a moderate labor reallocation from small firms (those with higher costs of switching lenders) to large firms in environmentally exposed sectors